Knowledge Production Practices and Attributes at University of Zambia School of Medicine - Kanyengo, Christine Wamunyima (Edulib, 2022)
Knowledge production practices and attributes of faculty are important in academia. The aim of the paper was to investigate the production, diffusion and use of knowledge products at University of Zambia School of Medicine. A survey methodology was adopted for the study; with data collected through semi-structured questionnaires. Using SPSS, data was analysed by simple descriptive statistics and Ms Excel for presentation into figures and tables. The results indicate the knowledge that is produced fits into the framework of knowledge produced by academia; the knowledge is produced, diffused and used frequently. The sources of information used in the knowledge production process are mostly from the internet and the university library. The knowledge is ethically and peer reviewed; frequently produced, utilised and diffused mostly through journals and books. The study concludes that the three processes of knowledge production, diffusion and use are frequently carried out at the University of Zambia School of Medicine.